Polemic of Halal Industry Trends in Idonesia: Between Legalization and Profanation in The Perspective of Maslahah Mursalah - Munawiroh, Afifatul (Program Studi Hukum Keluarga Islam, 2024)
This paper is based on library research or literature studies. The theme taken in this study is the Halal Industry in Indonesia. This research focuses on digging in depth regarding the ongoing polemic regarding the halal industry after the legalization of halal product guarantees contained Peraturan Pemerintah No. 39 Tahun 2021 Tentang Penyelenggaraan Bidang Jaminan Produk Halal. Even though it has been ratified, the reality in society still often arises debate regarding the urgency of enacting these regulations. The emphasized study includes whether the urgency of guaranteeing halal products is due to community initiatives, government interests, or simply wanting to match trends in other countries. There are two important questions in this research. First, what is the urgency of having halal products in Indonesia? Second, what is the polemic map of the application of the Halal Product Guarantee Law in Indonesia? With a juridical state approach to explain the reasons that require the existence of a halal product industry and the pros and cons of implementing halal product guarantees in Indonesia. The results in this study are that the ratification of regulations related to halal product guarantees has had an impact on the diversity of people in Indonesia. The existence of pros and cons after mandatory halal certification is the reason that the implementation of the halal industry in Indonesia still favors one group, has not provided aspects of benefit to all Indonesian citizens.